The white giraffe - St. John, Lauren, 1966- (Dial Books for Young Readers/Walden Media, 2007)
After a fire kills her parents, eleven-year-old Martine must leave England to live with her grandmother on a wildlife game reserve in South Africa, where she befriends a mythical white giraffe.